Political Patronage, Audit Quality and the Properties of Analysts' Earnings Forecasts in Malaysia - Gist, Willie; Abdul Wahab, Effiezal (American Accounting Association, 2021)
Based on a sample of 2,034 Malaysian listed firm-year observations for the period 2007–2014, this study shows a negative relationship between dimensions of political patronage (i.e., politically connected firms and the percentage of Bumiputera directors) and analysts' earnings forecast accuracy. Furthermore, the study documents a positive relationship between Bumiputera directors and earnings forecast dispersion. These results suggest that the political patronage of firms is associated with low-quality earnings. We also find that measures of high audit quality are associated with high financial reporting quality and that this is evident in firms with high audit quality showing a weaker negative (positive) relationship between forecast accuracy (dispersion) and political connections and high levels of Bumiputera directors. Overall, the findings suggest that high audit quality plays an important role in mitigating agency costs of information asymmetry by improving the financial information environment.